2016
DOI: 10.1002/pd.4979
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of susceptibility loci for neurodevelopmental disorders – genetic counseling and pregnancy outcome in 57 cases

Abstract: The diagnosis of a SL did not seem to be a reason for termination of pregnancy. Most patients were able to cope with the uncertainty and were interested in both prenatal and postnatal actionability of SL. Long-term follow-up is crucial to assess the actual risks for neurodevelopmental disorders, especially in families with unremarkable history. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
1
19
1
Order By: Relevance
“…As shown in our study, fetuses with SL can be found in ultrasound normal or soft marker group, although they were live born with normal phenotype, long-time follow-up is crucial to assess the actual risks for neurodevelopmental disorders. 35 Chromosomal microarray analysis is of great value not only for detecting submicroscopic anomalies but also cytogenetic abnormalities with unknown origins, such as small supernumerary marker chromosomes (sSMC), whose clinical phenotype and prognosis depend on the chromosomal origin. sSMC were reported to be associated with AMA.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in our study, fetuses with SL can be found in ultrasound normal or soft marker group, although they were live born with normal phenotype, long-time follow-up is crucial to assess the actual risks for neurodevelopmental disorders. 35 Chromosomal microarray analysis is of great value not only for detecting submicroscopic anomalies but also cytogenetic abnormalities with unknown origins, such as small supernumerary marker chromosomes (sSMC), whose clinical phenotype and prognosis depend on the chromosomal origin. sSMC were reported to be associated with AMA.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2017 special topic issue, the challenges associated with prenatal genetic counseling for neurodevelopmental disorders were described in a study by Gouvaerts and colleagues . They analyzed outcomes for 57 Dutch fetuses that had been identified as having susceptibility loci for neurodevelopmental disorders following whole genome arrays.…”
Section: Advances In Research On Autism Spectrum Disordermentioning
confidence: 99%
“…Variants in genes associated with the following biological processes are thought to play a role in the etiology of ASD: In the 2017 special topic issue, the challenges associated with prenatal genetic counseling for neurodevelopmental disorders were described in a study by Gouvaerts and colleagues. 20 They analyzed outcomes for 57 Dutch fetuses that had been identified as having susceptibility loci for neurodevelopmental disorders following whole genome arrays. Of the 57, 34 had anomalies detected by ultrasound examination and 23 did not.…”
Section: Expanded Non-invasive Prenatal Testing: Advantages Challementioning
confidence: 99%
“…How should providers communicate such incidental findings, and how expectant couples process and are affected by such information in their decision‐making has not yet been completely investigated. In this issue, the findings in a Dutch cohort are presented, in which the diagnosis of neurodevelopmental susceptibility loci was reported to the parents . Expert post‐test genetic counseling allowed the couples to translate such information into prenatal and postnatal action.…”
mentioning
confidence: 99%
“…In this issue, the findings in a Dutch cohort are presented, in which the diagnosis of neurodevelopmental susceptibility loci was reported to the parents. 6 Expert post-test genetic counseling allowed the couples to translate such information into prenatal and postnatal action.…”
mentioning
confidence: 99%